DNA Methylation Signatures in Development and Aging of the Human Prefrontal Cortex - Numata, Shusuke; Ye, Tianzhang; Hyde, Thomas M.; Guitart-Navarro, Xavier; Tao, Ran; Wininger, Michael; Colantuoni, Carlo; Weinberger, Daniel R.; Kleinman, Joel E.; Lipska, Barbara K. (American journal of human genetics, 2012)
The human prefrontal cortex (PFC), a mastermind of the brain, is one of the last brain regions to mature. To investigate the role of epigenetics in the development of PFC, we examined DNA methylation in ∼14,500 genes at ∼27,000 CpG loci focused on 5′ promoter regions in 108 subjects range in age from fetal to elderly. DNA methylation in the PFC shows unique temporal patterns across life. The fastest changes occur during the prenatal period, slow down markedly after birth and continue to slow further with aging. At the genome level, the transition from fetal to postnatal life is typified by a reversal of direction, from demethylation prenatally to increased methylation postnatally. DNA methylation is strongly associated with genotypic variants and correlates with expression of a subset of genes, including genes involved in brain development and in de novo DNA methylation. Our results indicate that promoter DNA methylation in the human PFC is a highly dynamic process modified by genetic variance and regulating gene transcription. Additional discovery is made possible with a stand-alone application, BrainCloudMethyl.